Microstructure evolution of cold-worked Zircaloy-4 under 20 mev Cu ion irradiation. (3rd April 2019) - Naceri, S. E.; Izerrouken, M.; Ishaq, A.; Guittoum, A.; Sari, A.; Khereddine, A.; Kadouma, M.; Menchi, O.; Ghamnia, M.
ABSTRACT: Cold-worked Zircaloy-4, used for the fuel grid of research reactors, was irradiated with 20 MeV Cu ions at different doses varying from 0.007 to 0.15 displacements per atom (dpa) at room temperature. The microstructure evolution was investigated by grazing X-ray diffraction and positron annihilation spectroscopy techniques (PAS). The mechanical properties were studied using nanoindentation. The microstrain, S parameter and nanohardness present similar behaviour. They all increase rapidly during the beginning of irradiation (first stage) and reach saturation value at 0.15 dpa. The experimental results reveal radiation-induced lattice distortion along the (110) direction indicating an anisotropic displacement energy.